Does NOTA Affect Voter Turnout? Evidence from State Legislative Elections in India - Mandal, Arindam; Mandal, Biswajit; Bhattacharjee, Prasun (Asian Journal of Economic Modelling, 2017)
This paper explores the impact of introduction of the ‘None of the Above’ (NOTA) option in Indian legislative elections. NOTA was introduced as a ballot option following the Supreme Court ruling in 2013 based on the argument that more choices to voters will enhance voter participation. We take advantage of the state-time variation in introduction of NOTA option in state legislative assembly elections in 2013 to study its impact on voter turnout. Using election data from five major Indian states between 2008 and 2013, we find evidences suggesting that NOTA may not have led to increased voter participation. However, our results are not conclusive.